Analysis Of The Contract System In Leasing From Conventional And Sharia Perspectives - Lisa Purnama Putri; Zulfikar Hasan; Mahadir Mohamad (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2026)
This study aims to find out about this leasing business in terms of both Islamic and conventional law. The type of research used is the qualitative method of library research as the completion methodology, namely by collecting library data, reading and taking notes, and then managing the research material. Leasing financing or leasing business is a financing activity in the provision of capital goods that are regularly paid for a certain period of time. This leasing consists of two types, namely sharia-based leasing and conventional-based leasing. There are a few differences between the two types of leasing. Many companies are interested in using this leasing financing. Because using leasing financing does not require guarantees from the company. With this leasing, companies, especially new companies, can be helped from a managerial perspective.